Improved Outcomes with Intensity Modulated Radiation Therapy Combined with Temozolomide for Newly Diagnosed Glioblastoma Multiforme. (19th January 2014) - Aherne, Noel J.; Benjamin, Linus C.; Horsley, Patrick J.; Silva, Thomaz; Wilcox, Shea; Amalaseelan, Julan; Dwyer, Patrick; Tahir, Abdul M. R.; Hill, Jacques; Last, Andrew; Hansen, Carmen; McLachlan, Craig S.; et al.
Abstract : Purpose . Glioblastoma multiforme (GBM) is optimally treated by maximal debulking followed by combined chemoradiation. Intensity modulated radiation therapy (IMRT) is gaining widespread acceptance in other tumour sites, although evidence to support its use over three-dimensional conformal radiation therapy (3DCRT) in the treatment of gliomas is currently lacking. We examined the survival outcomes for patients with GBM treated with IMRT and Temozolomide. Methods and Materials . In all, 31 patients with GBM were treated with IMRT and 23 of these received chemoradiation with Temozolomide. We correlated survival outcomes with patient functional status, extent of surgery, radiation dose, and use of chemotherapy. Results . Median survival for all patients was 11.3 months, with a median survival of 7.2 months for patients receiving 40.05 Gray (Gy) and a median survival of 17.4 months for patients receiving 60 Gy. Conclusions . We report one of the few series of IMRT in patients with GBM. In our group, median survival for those receiving 60 Gy with Temozolomide compared favourably to the combined therapy arm of the largest randomised trial of chemoradiation versus radiation to date (17.4 months versus 14.6 months). We propose that IMRT should be considered as an alternative to 3DCRT for patients with GBM.